Categorical and metaphysical dispersion in Aristotle - Zingano, Marco (Estudios de Filosofía, 2002)
If we consider the statement of the Ethics Eudemia 18, Aristotle seems to be far from metaphysics because, having adopted a thesis on the original dispersion of being in the different categories, he had no way of thinking about a single science of being, since, apparently, had not yet applied as it is a notion of focal unit of meaning, which was conceived, precisely in EE, to explain the phenomenon of friendship. When the pros hen legesthai is applied to being then a unique metaphysics or science of being will be possible outside the Platonic pitch. Until that time, however, Aristotle is without metaphysics. In this article, I try to investigate what such a period of metaphysical disenchantment for Aristotle looks like and what traces it eventually left us, from this time.